(untitled) (Bangladesh Journal of Zoology, 2018)
Sawfishes are the most endangered cartilaginous fishes on earth with alarming global population decline due to by-catch and socio-economic value. A study on elasmobranch diversity in one of the landing sites of Bangladesh observed annual sawfish captures (n = 5) adjacent to the Sundarbans, the largest mangrove forests in the world, between June 2017 and March 2018. Only largetooth sawfish Pristis pristis was recorded in this study. Data were collected from interviews with fishermen, literature review, media reports and through monthly fish landing record sheet used during the study period. Findings of this study shows that 80% (n = 4) sawfish species were captured in dry season (November to March) and 20% (n = 1) in wet season (June to October). Findings from the semi-structured interviews (n = 50) reported that 54% of the respondents were not aware of the value (ecological as well as economic) of sawfish species whereas 46% of the respondents mentioned sawfish as an important species as its flesh used to cure cancer. Although this report does not reflect the annual capture of sawfish from all over the country, this catch pattern is alarming and needs immediate action to develop a monitoring programme to assess sawfish landings in this area. Priority research is also needed to understand sawfish life history, identify their critical habitats and raise awareness to conserve sawfish species. Bangladesh J. Zool. 46(2): 255-262, 2018